Different Volumetric Ratios for Preparing Ternary Cu2SnS3 Thin Films using Fully Controlled System of Spray Pyrolysis - Conf18, Physics; Hadi, Zaid L.; Chiad, Bahaa T. (Iraqi Journal of Science, 2019)
Ternary thin films have been clearly deposit using fully computerized system of spray pyrolysis technique onto glass substrates maintained at 310±5 °C. A mixture of an aqueous solution of thiourea, tin chloride dehydrate and copper chloride was used as spraying liquid. The optimumvolumetric ratio of mixing was found to be [S/(Cu+Sn)=1] at pH =1.5, in the present work. XRD examination was revealed CTS in a monoclinic phase. Number platform speeds were employed in the spraying process. XRD peaks were described at 2? = 28.39°, 33.02°, 47.34°, and 56.39° corresponding to , , , and , respectively. The FTIR investigations were certified a numeral of the chemical bond of Cu-, Sn- and S-. The grain size was observed in the range of nanosized using Scherrer formula. Studying surface morphology of CTS films reveals a uniform coating on the substrates which approved by SEM investigations.